Fire transforms effects of terrestrial subsidies on aquatic ecosystem structure and function - Christopher B. Wall; Cody J. Spiegel; Evelyn M. Diaz; Cindy H. Tran; Alexia Fabiani; Taryn Y. Broe; Elisabet Perez‐Coronel; Sara L. Jackrel; Natalie Mladenov; Celia C. Symons; Jonathan B. Shurin (Global Change Biology, 2024)
Fire can lead to transitions between forest and grassland ecosystems and trigger positive feedbacks to climate warming by releasing CO 2 into the atmosphere. Climate change is projected to increase the prevalence and severity of wildfires. However, fire effects on the fate and impact of terrestrial organic matter (i.e., terrestrial subsidies) in aquatic ecosystems are unclear. Here, we performed a gradient design experiment in freshwater pond mesocosms adding 15 different amounts of burned or unburned plant detritus and tracking the chronology of detritus effects at 10, 31, 59, and 89 days. We show terrestrial subsidies had time‐ and mass‐dependent, non‐linear impacts on ecosystem function that influenced dissolved organic carbon (DOC), ecosystem metabolism (net primary production and respiration), greenhouse gas concentrations (carbon dioxide [CO 2 ], methane [CH 4 ]), and trophic transfer. These impacts were shifted by fire treatment. Burning increased the elemental concentration of detritus (increasing %N, %P, %K), with cascading effects on ecosystem function. Mesocosms receiving burned detritus had lower [DOC] and [CO 2 ] and higher dissolved oxygen (DO) through Day 59. Fire magnified the effects of plant detritus on aquatic ecosystem metabolism by stimulating photosynthesis and respiration at intermediate detritus‐loading through Day 89. The effect of loading on DO was similar for burned and unburned treatments (Day 10); however, burned‐detritus in the highest loading treatments led to sustained hypoxia (through Day 31), and long‐term destabilization of ecosystem metabolism through Day 89. In addition, fire affected trophic transfer by increasing autochthonous nitrogen source utilization and reducing the incorporation of 15 N‐labeled detritus into plankton biomass, thereby reducing the flux of terrestrial subsidies to higher trophic levels. Our results indicate fire chemically transforms plant detritus and alters the role of aquatic ecosystems in processing and storing carbon. Wildfire may therefore induce shifts in ecosystem functions that cross the boundary between aquatic and terrestrial habitats.